Utilisation of pullulan active packaging incorporated with curcumin and pullulan mediated silver nanoparticles to maintain the quality and shelf life of broiler meat - Khan, Muhammad Jamshed; Ramiah, Suriya Kumari; Selamat, Jinap; Shameli, Kamyar; Sazili, Awis Qurni; Mookiah, Saminathan (Taylor & Francis, 2022)
Broiler meat can provide an appropriate environment for the microbial intensification, resulting in the lipid and protein oxidation and physico-chemical degradation. The utilisation of the anti-oxidants prevents meat degradation and human health challenges by preventing meat physico-chemical characteristics. Pullulan active packaging incorporated with green silver nanoparticles, as anti-oxidants, has not been reported in broiler meat preservation. Therefore, the impact of pullulan active packaging, incorporated with curcumin and pullulan mediated silver nanoparticles (C-AgNPs, P-AgNPs) on broiler meat was determined in the current study for 14 days of refrigerated storage at 4 ± 1 °C. A total of 120 broiler birds were reared for clean meat production and divided into 4 treatment groups (PF-CTRL, PF-C-AgNPs, PF-P-AgNPs, PF-M-AgNPs). Pullulan active packaging maintained meat textural attributes and pigment stability and breast muscle pH (6.11). Broiler meat treated with pullulan active packaging incorporated with curcumin arbitrated AgNPs (PF-C-AgNPs) indicated significantly higher oxidative stability (p = .000), water holding capacity (p = .002), expressible fluids (p = .000), and shear force values (p = .000) along with significantly lower cooking losses (p = .000), pH (p = .000), and shear force energy (p = .000) as compared to the control (CTRL) and other treatment groups. Broiler breast meat samples treated with pullulan active packaging expressed a “lighter” appearance (53.61 ± 3.64) during the refrigerated storage of 14 days. Moreover, significant differences were recorded in the oxidative stability/MDA (mg/kg) concentrations amongst the controlled and the treated groups on day 7th (p = .000) and day 14th (p = .000) of refrigerated storage. The current study confirms that the pullulan active packaging, incorporated with curcumin arbitrated silver nanoparticles (PF-C-AgNPs) followed by pullulan active meat packaging incorporated with pullulan mediated silver nanoparticles (PF-P-AgNPs) maintained the textural and physico-chemical meat attributes along with minimal oxidative rancidity in 14 days of storage. It is concluded that PF-C-AgNPs and PF-P-AgNPs can be a safer antioxidant alternate to preserve broiler meat quality and oxidative stability with a prolonged shelf life.